A lay person’s guide to medicine: Book review - Shankar, P Ravi (Journal of College of Medical Sciences-Nepal, 2010)
DOI: 10.3126/jcmsn.v6i2.3620 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 62-63